TULISAN ARAB: PEMBINA TAMADUN ISLAM DI NUSANTARA - Cho, Taeyoung (Siddhayatra, 2018)
This paper describes the role of Arabic script on a view of establishing Islamic civilizationin Indonesian archipelago. Arabic script, apart from a tool for writing, its characteristicis so intensive to symbolize Islamic civilization. The arrival of Islamic civilization intothe archipelago has not only spread the religion, but also influenced the change of socialsystem in which Arabic script wrote the various spheres of Islamic civilization and transferredthem into the local communities. The appearance of variant graphemes into the Arabic-based local scripts (Jawi, Pgon, Srang, and Buri Wolio) is a result from the modificationof Arabic script to the local languages for transmitting the elements of Islamic civilizationto the contexts of local communities. In other words, Arabic script shifted Indonesianarchipelago from the age of Jahiliah to the age of Islamic civilization.